KAJIAN POLA-HEMAT PEMBERIAN AIR IRIGASI - Nurrochmad, Fatchan (Civil Engineering Forum Teknik Sipil, 2007)
Paddy is a semiaqutic crop that is also adaptic to water lacking condition such as paddy gogo. As common practice in Indonesia, farmers use excessive amount of irrigation water for their paddy field, hoping to yield maximum amount of harvest. Such practice result in the problem of irrigation water supply due to significant amount of irrigation water requirement. However, paddy harvest is actually influenced by the crop variety, water management, soil nutrient availability and land management. A study of irrigation watering pattern is required to obtain irrigation water saving based on the paddy botanical characteristics related to soil nutrient appropriate management in order to gain optimal harvest. This study applied the pattern of irrigation water supply to five plots of 2x3 m2 model consist of 7x11 points, filled with sandy clay soil. The pattern were continuous flooding (PTM), semi flooding – moisturing – semi flooding (SPS), semi flooding - moisturing (SPP), semi flooding – semi moisturing (SPSP) and flooding - moisturing (PP). Three seeds were planted in each point of PTM and PP pattern, and one seed for each of other pattern. Nutrient were given for every paddy plot at the 8th , 25 th and 40 th day of cultivation. Result of this study showed irrigation water used, which did not include land preparation, and harvest under the PTM, SPS, SPP, SPSP and PP pattern were 5385 l and 3,9 kg, 4290 l and 3,9 kg, 4530 l and 4,3 kg , 4265 l and 3,0 kg and 3915 l and 4,9 kg respectively. PP pattern used the least amount of irrigation water but yielded the filler to yield the optimum result, based on the paddy botanical characteristic and appropriate soil nutrient management. It also saved 33,8 % irrigation water in compare to the conventional practice based on the standard stated by the Ministry of Public Works.